Preventing Corporate Corruption
XIV, 533 p. 2 illus.
Keywords: This book presents the results of a two-year international research project conducted by five academic institutions, under the co-ordination of ISPAC, in co-operation with the United Nations Office on Drugs and Crime (UNDOC) to investigate and provide solutions for reducing bribery and corruption in corporations and institutions. It starts with an empirical case study on the effectiveness of a set of self-regulation rules adopted by multinational companies in the energy sector. Second, it explores the relationships between domestic criminal law and self-regulation. Third, it examines guidelines for the adoption of compliance programs developed by international institutions, to serve as models for the future. The principle result of the book is a three-pronged Anti-Bribery Compliance Model (so called ABC Model), intended as a corruption prevention tool to be adopted by private corporations. It provides a common, research-based standard for anti-bribery compliance programs, with international applications. This book will be of interest to researchers studying Criminology and Criminal Justice, particularly in the areas of organized crime and corruption, as well as related areas like Business Ethics and Comparative International Law.